Unleashing Effective Models of Collaboration for Rainwater Harvesting: Experiences from Nepal - Yadav, Maheshwar Prasad; Aithal, P. S.; Yadav, Neelam; Karki, Tej Bahadur (Darul Yasin Al Sys, 2024)
Background: Rainwater harvesting (RWH) is an age-old practice of a localized renewable and alternate source of water supply to meet the growing demand of people in developing countries like Nepal. Thus, the effective models of collaboration for providing water services through RWH is a pathway to the sustainable water management of the nation leading to achieving SDGs. Purpose: The paper aims at unleashing effective models of collaboration for RWH in the context of the rural areas of Nepal. Methodology: The study comprises a descriptive cum analytical research design based on both primary and secondary data. The necessary primary data were collected by conducting a field survey using a semi-structured questionnaire on a sample of 38 communities/projects having RWH systems while the secondary data were collected through relevant publications. The csollected data were analyzed using statistical tools through SPSS to derive results leading to major findings of the study. Analysis/Results: The study concluded that a collaborative plan provides a ground to get contributions from different stakeholders and increase their sense of ownership. The collaboration with the local government ensures co-financing and involvement in planning and monitoring and increases prospects for support to required rehabilitation in the future. Community engagement from planning to implementation to managing the systems ensures the system's functionality and sustainability, leading to caretakers’ management and promoting income-generating activities using waste/overflow water from the system. The multiple uses of water services (MUS) provide a basis for livelihood enhancement leading to regular payment of tariffs. The caretakers’ management ensures to fix minor repairs promptly as needed. A combination of monitoring and eval_uation with different stakeholders during implementation and afterward ensures efficient and effective implementation and sustainability of the RWH system. Originality/Value: No such study uses recent data related to effective models of collaboration for RWH in the context of the rural areas of developing countries like Nepal is accessible. The paper, therefore, is valuable for users’ committees, development actors, academia, and policymakers to create effective models of collaboration for RWH. This work may potentially be useful to academia for future studies. Future avenue: The extension of this study can be made by incorporating an analysis of diverse applications of artificial intelligence (AI) in the water management sector in future studies.